2006
DOI: 10.1002/art.21869
|View full text |Cite
|
Sign up to set email alerts
|

Solid malignancies among patients in the Wegener's granulomatosis etanercept trial

Abstract: Objective. Etanercept is a soluble fusion protein designed to inhibit tumor necrosis factor (TNF). During the Wegener's Granulomatosis Etanercept Trial (WGET), a placebo-controlled trial of etanercept given in addition to standard therapy for remission induction and maintenance, more solid malignancies were observed in the etanercept group than in the group treated with standard therapy alone. This study was undertaken to further explore the potential association between anti-TNF therapy and the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
3
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 186 publications
(106 citation statements)
references
References 34 publications
3
94
3
6
Order By: Relevance
“…Subsequently, anti-TNF-a strategies were successfully applied to other related rheumatologic diseases (12) and then to inflammatory bowel disease (IBD) (13). However, anti-TNF-a therapy was not effective in ANCA vasculitis (14) and multiple sclerosis (MS) (15). A number of different strategies have been used to achieve therapeutic outcomes by cytokine manipulation.…”
Section: Biologic Approaches To Cytokine Therapeutic Manipulationmentioning
confidence: 99%
“…Subsequently, anti-TNF-a strategies were successfully applied to other related rheumatologic diseases (12) and then to inflammatory bowel disease (IBD) (13). However, anti-TNF-a therapy was not effective in ANCA vasculitis (14) and multiple sclerosis (MS) (15). A number of different strategies have been used to achieve therapeutic outcomes by cytokine manipulation.…”
Section: Biologic Approaches To Cytokine Therapeutic Manipulationmentioning
confidence: 99%
“…Studies in specific populations, however, have suggested some increased risk. For example, a study of ETA in patients with Wegener's granulomatosis, all of whom had previously received treatment with cyclophosphamide, reported an excess of solid tumors [103].…”
Section: Non-infectious Adverse Consequences Of Tnfα Antagonists Malimentioning
confidence: 99%
“…[33][34][35][36] Particularly, the risk of solid tumor development is further increased in patients who concurrently use cyclophosphamide and anti-TNF agents. 37 Imai et al has shown that patients with low NK activity have a higher risk of cancer development during a follow-up period of 11 years. 38 The interactions between proliferating tumor cells, human leukocyte antigen system and NK-receptors have also been postulated to be responsible for tumor survival and progression.…”
Section: Discussionmentioning
confidence: 99%